Association between serum sclerostin levels and chronic kidney disease–mineral and bone disorders in hemodialysis patients - Vo, Thi Hoai Huong; Nguyen, Hoang Thanh Van; Phan, Thi Minh Phuong (Tạp chí Y Dược Huế, 2026)
ABSTRACT Objective: (1) To evaluate the mineral and bone disorders, bone mineral density, and serum sclerostin levels in patients with chronic kidney disease undergoing maintenance hemodialysis, compared with a healthy control group with normal renal function. (2) To evaluate the relationship between serum sclerostin concentration and CKD – Mineral and Bone disorders (CKD-MBD) in hemodialysis patients. Patients and methods: This is a cross-sectional descriptive study on 51 CKD hemodialysis patients at the Department of Nephrology - Musculoskeletal, Hue Central Hospital and 60 healthy people with normal kidney function regularly came for health check-ups at the Internal Medicine Clinic of Hue University of Medicine and Pharmacy from April 2023 to 2025. Results: The study population in our research consisted of two groups: a control group comprising 60 individuals, including 25 males and 35 females, with a mean age of 49.27 ± 10.98; and a G5HD group including 31 males and 20 females, with a mean age of 47.92 ± 14.88. The difference in age between the two groups was not statistically significant (p>0.05). The mean serum calcium (adjusted for serum albumin), phosphorus, and PTH concentrations in 52 patients undergoing hemodialysis in the study were 2,330 ± 0.218 mmol/l; 2,034 ± 0.588 mmol/l, and 711,318 ± 905,620 pg/dL, respectively. In terms of blood calcium disorders, 11.76% of patients had hypocalcemia and about 1/5 had hypercalcemia. Our study found that 86.27% had hyperphosphatemia and more than 90% of G5HD patients had increased serum PTH levels. Regarding bone density in the G5HD group, the mean BMD at the femoral neck, total femur, and lumbar spine were 0.820 ± 0.221; 0.840 ± 0.194 and 1.003 ± 0.194 g/cm2, respectively. The mean serum sclerostin concentration in the control group of our study was 359.52 ± 168.21 pg/mL. The G5HD groups exhibited significantly higher serum sclerostin level compared to the control group (p < 0.05); the mean concentrations was 937.152 ± 881.105 pg/ml. Serum sclerostin concentrations in hemodialysis patients were significantly negatively correlated with serum PTH and bone mineral density at the femoral neck and total hip (p<0.05). Conclusion: In conclusion, according to our study, CKD-MBD are common in patients with end-stage renal disease undergoing maintenance hemodialysis. Serum sclerostin levels were significantly higher in the hemodialysis group compared to healthy controls. Regarding the association between sclerostin and mineral-bone disorders as well as bone mineral density in hemodialysis patients, our findings demonstrate that serum sclerostin levels were significantly and inversely correlated with PTH levels and bone mineral density at the femoral neck and total hip.